"Being Able to Speak": What Individuals in Jail Perceived as Helpful about Participating in Alcohol-Related Brief Interventions. Issue 3 (July 2018) - Owens, Mandy D.; Kirouac, Megan; Hagler, Kylee; Rowell, Lauren N.; Williams, Emily C.
Background: A significant proportion of individuals within the criminal justice system meet criteria for a substance use disorder. Treatments for individuals who are incarcerated with substance use disorders show minimal to no benefit on postrelease outcomes, suggesting a need to improve their effectiveness, particularly those that can be delivered in a brief format. The purpose of this study was to describe what individuals in jail with substance use disorders perceived as being helpful about 2 brief alcohol-focused interventions, which can be used to inform future treatments with this population. Methods: Data came from a parent study where 58 individuals in jail with substance use disorders received either a motivational or educational intervention focused on alcohol and other substance use and then completed a questionnaire assessing what was most and least helpful about the interventions. Qualitative responses were coded using a grounded theory approach. Results: Results indicated that participants from both interventions reported that receiving individualized attention and talking one-on-one with someone was helpful, and that the interventions were encouraging and elicited hope. There also were specific components from each intervention that participants said were beneficial, including the opportunity to discuss plans for postrelease and to learn about addiction from psychoeducational videos. Participants noted areas for improving future interventions. Suggestions from participants were to offer tangible resources upon release, make session lengths flexible, and reduce assessment burden during research interviews. Conclusions: Findings align with established approaches for working with marginalized groups, namely, community-based participatory research methods and shared decision-making models for treatment. This study provided a voice to individuals in jail with substance use disorders, a group often underrepresented in the literature, and may offer an initial look at how to improve treatments for this high-risk population.